CURRENT STATE OF FINANCIAL SECURITY OF BANKING INSTITUTIONS AND ITS INNOVATIVE WAREHOUSE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The actuality of the study is due to the extreme importance of the banking system in the functioning of the country's economy, since the financial stability and reliability of banking institutions creates conditions for the development of the entire economy in the future. Of particular importance is the issue of ensuring the financial security of banking institutions in Ukraine, which is simultaneously affected by such threats as military aggression, digitalization, and the need to adapt to EU norms as a candidate for membership in the European Community. The purpose of the article. The purpose of the study is to identify the current state of financial security of commercial banks in Ukraine in the context of active use of banking innovations in the activities of such financial institutions.Metods. In order to achieve this goal, the authors used such research methods as analysis and synthesis, comparison, tabular method, systematization method, and coefficient analysis.Results. In the article the authors study the content of financial security of banking institutions and its main elements. The main indicators of financial security in the context of profitability of banking institutions in Ukraine are calculated. The place of the innovation and investment component in ensuring the financial security of banking institutions is determined and its current status is assessed.Conclusiоns. The role of banking innovations in ensuring the financial security of banking institutions is substantiated. It is determined that in order to ensure the financial security of banking institutions, taking into account its innovative component, in modern conditions it is necessary to combine effective management of the innovative activities of a banking institution. This will increase the profitability of commercial banks by increasing the customer base, improving the quality of customer service, and will ensure the growth of competitiveness of domestic banking institutions.
Keywords: financial security, banking institutions, indicators of financial security, banking innovations, investment security, threats, digitalization.